KELAYAKAN MEDIA SCRAPBOOK PADA SUBMATERI PERAN TUMBUHAN DI BIDANG EKONOMI KELAS X SMA - Siti Sahara; Wolly Candramila; Titin Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
Abstract This study aimed to find out the result of the feasibility of the scrapbook on the Sub Material of the Plant Roles in Economic. The method used was a descriptive method. Furthermore,the feasibility of the scrapbook media assessed by 5 media experts got a CVR value of 0.99 which was in accordance with minimum CVR value of Lawshe so that the scrapbook media is suitable for use as a learning medium on sub matter the role plants in economic field. Keyword: Appropriateness, Media, Scrapbook